Wetspun polymeric fibrous systems as potential scaffolds for tendon and ligament repair, healing and regeneration - Rocha, Joana (2022)
Tendon and ligament traumatic injuries are among the most common diagnosed musculoskeletal problems. Such injuries limit joint mobility, reduce musculoskeletal performance, and most importantly, lower people’s comfort. Currently, there are various treatments that are used to treat this type of injury, from surgical to conservative treatments. However, they’re not entirely effective, as reinjures are frequent and, in some cases, fail to re-establish the lost functionality. Tissue engineering (TE) approaches aim to overcome these disadvantages by stimulating the regeneration and formation of artificial structures that resemble the original tissue. Fabrication and design of artificial fibrous scaffolds with tailored mechanical properties are crucial for restoring the mechanical function of the tissues. Recently, polymeric nanofibers produced by wetspinning have been largely investigated to mimic, repair, and replace the damaged tissue. Wetspun fibrous structures are extensively used due to their exceptional properties, such as the ability to mimic the native tissue, their biodegradability and biocompatibility, and good mechanical properties. In this review, the tendon and ligament structure and biomechanics are presented. Then, promising wetspun multifunctional fibrous structures based on biopolymers, more specifically polyhydroxyalkanoates (PHA), polycaprolactone (PCL), and polyethylenes, will be discussed, as well as reinforcing agents such as cellulose nanocrystals (CNC), nanoparticles, and growth factors.